The association between social support networks and maternal employment: a comparison of western German, eastern German, and migrant mothers of preschool-aged children - Mareike Bünning (Community, Work & Family, 2017)
A lack of adequate childcare can delay mothers' return to the labor market after childbirth. This paper examines whether social support with childcare by kin and friends facilitates maternal employment in the first 72 months after childbirth. Using data from the German Socio-Economic Panel (SOEP) 1993–2009, a comparison of natives (n0.167em=0.167em1409) and migrants (n0.167em=0.167em411) in corporative-conservative western Germany with mothers in former socialist eastern Germany (n0.167em=0.167em528) shows that kinship support is positively associated with maternal employment when public childcare is limited. Western German and migrant mothers return to work sooner if they are surrounded by kin. But kin do not provide support for maternal employment in eastern Germany, where public childcare is more easily accessible and continuous female employment is a prevalent social norm. Friendship networks, by contrast, are most valuable for maternal employment if they complement public childcare. – – Le retour des mères sur le marché de travail peut être retardé à cause d'un manque de services de garde adéquats. Cet article examine si le soutien social à la garde d'enfant par la famille et des amis facilite le retour à l'emploi des mères dans les 72 premiers mois suivant l'accouchement. En utilisant les données du panel socio-économique allemand (SOEP) entre 1993 et2009, nous comparons des natifs (n = 1409) et des immigrants (n = 411) en l'Allemagne de l'Ouest (corporatiste-conservatrice) d'une part, et, des mères dans l'ancienne Allemagne de l'Est socialiste (n = 528) d'autre part. Notre analyse montre qu'un soutien familial facilite le retour à l'emploi lorsque l'offre de services de garde publics est limitée. Les mères d'Allemagne de l'Ouest et les immigrantes retournent au travail plus tôt si elles sont soutenues par leur famille. Par contre, en Allemagne de l'Est, où les services de garde publics sont plus facilement accessibles et l'emploi en continu des femmes est une norme sociale davantage répandue, le soutien de la famille ne joue pas un rôle significatif. En revanche, les réseaux d'amis sont précieux pour les activités professionnelles des mères, s'ils permettent de complémenter les services de garde publics.
Keywords: 330; maternal employment; childcare arrangements; social support; social networks; family policy